Factors associated with applicant performance on the Saudi Pharmacist Licensure Examination (SPLE) - Wael A. Alghamdi; Tahani M. Almeleebia; Mona A. Almanasef; Khalid M. Orayj (Elsevier, 2024)
Background: Limited data are available on factors that are associated with passing rates for the Saudi Pharmacist Licensure Examination (SPLE). The aim of this study is to investigate student characteristics and academic performance characteristics that may predict their success on SPLE. Methods: This was a single-institution retrospective cohort study, which included pharmacy graduates from 2019 to 2021. Demographic, academic, and SPLE data were collected for each graduate. Binary logistic regression was used to explore the association between potential predictors and first-time SPLE pass status. A stepwise regression was then performed to develop multiple logistic models. Results: A total of 494 graduates were included in the study. Females, PharmD graduates, and on-time graduation had higher odds of passing SPLE (P = 0.0065, P = 0.0003, and P < 0.0001, respectively). For each 0.5 increase in GPA, the odds of passing SPLE increase by 3.5 times (OR 3.53; 95 % CI, 2.83-4.42; P < 0.0001). Of the tests taken prior to university admission, the overall high school score, general aptitude test (GAT) score, and qualifying score were significantly associated with higher SPLE first-time pass rates. When multiple logistic regression analysis was performed, GPA and GAT scores were the only significant predictors for higher SPLE first-time pass rates (P < 0.0001 and P = 0.0002, respectively). Conclusion: The current research has shown that there is an association between higher SPLE first-time pass rates and several factors, most importantly the GPA and GAT score. Further research is needed, as it has the potential to inform the decision when reviewing pharmacy admission criteria.